Effect of Angular Velocity on Frictional Contact Characteristics of the V-belt Transmission System - Liu Wenying (Jixie chuandong)
The finite element model of the V-belt transmission system is established,and the friction and contact characteristic of the V-belt transmission system under the condition of different angular velocity,friction coefficient is analyzed,the effect of frictional contact characteristics of the V-belt transmission system under the condition of different angular velocity,friction coefficient is studied.The results show that with angular velocity increasing,the contact force between the belt and pulley decreases;with contact degree increasing,the contact force between the belt and pulley increased;with friction factor increasing,the friction angle of the contact point decreases;with contact degree increasing,the friction angle of the contact point increased,and reached the maximum at the contact point out;from outer to inner,the belt and pulley contact stress and friction angle are different in different node along the radial direction,but both trends are basically identical.